Energy efficient Key Distribution for Wireless Sensor Networks - Ramu Kuchipudi, Ramu; Ahmed Abdul Moiz Qyser, Dr.; V V S S S Balaram, Dr. (International Journal of Engineering and Technology, 2018)
Key distribution in Wireless sensor networks is crucial whenever they deployed in critical applications. Cryptography is used to protect sensitive information from disclosure. Key management is important component in cryptography. Cryptography is not useful if keys are disclosed to attackers. Designing an efficient key management for sensor network is a difficult task because of scarcity of computing and memory resources. An efficient key distribution approach is proposed by using mobile agent paradigm rather than client server model. The proposed approach will use good features of both symmetric and asymmetric cryptography. Mobile Agents are used to generate public and private key pairs, update keys and revocation of keys. The proposed scheme in the first level will use mobile agents for public key dissemination and in second level sensor nodes can involve in constructing symmetric keys for secure communication through mutual authentication and encryption with those keys. The proposed method is implemented using NS2 Simulator and results are compared with existing similar methods in terms of evaluation parameters like throughput and resiliency. The proposed method is improved when it is compared with similar existing methods.Â